2013
DOI: 10.3390/soc3020158
|View full text |Cite
|
Sign up to set email alerts
|

A War of Words: Do Conflict Metaphors Affect Beliefs about Managing “Unwanted” Plants?

Abstract: Woody plants have increased in density and extent in rangelands worldwide since the 1800s, and land managers increasingly remove woodland plants in hopes of restoring pre-settlement conditions and/or improved forage for grazing livestock. Because such efforts can be controversial, especially on publicly owned lands, managers often attempt to frame issues in ways they believe can improve public acceptance of proposed actions. Frequently these framing efforts employ conflict metaphors drawn from military or lega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Advocates of risk reduction actions that affect aesthetic values (e.g. which includes most forest management practices) should be attentive to variation in aesthetic preferences across socially diverse landscapes (Ribe 1989, Nay andBrunson 2013). In the case of trade-offs involving air quality, our results provide empirical support for what many decision-makers and other wildfire risk mitigation practitioners know from personal experience-stakeholders may not distinguish 'bad' smoke (e.g.…”
Section: Management Implicationsmentioning
confidence: 59%
“…Advocates of risk reduction actions that affect aesthetic values (e.g. which includes most forest management practices) should be attentive to variation in aesthetic preferences across socially diverse landscapes (Ribe 1989, Nay andBrunson 2013). In the case of trade-offs involving air quality, our results provide empirical support for what many decision-makers and other wildfire risk mitigation practitioners know from personal experience-stakeholders may not distinguish 'bad' smoke (e.g.…”
Section: Management Implicationsmentioning
confidence: 59%
“…For example, a recent survey of residents of Montana, Wyoming, and Idaho found that rangelands in a natural shrub-steppe condition were viewed as less scenic than those that had undergone conifer encroachment. 6 If shrublands are under-appreciated, there is less chance of public pressure to halt conversion to other vegetation types or land uses.…”
Section: Unwanted No More: Land Use Ecosystem Services and Opportunmentioning
confidence: 99%
“…However, other scholars demonstrate that RELIGION metaphors have been used to dispute such sceptical arguments to present scientists as prophets capable of interpreting signs (Foust and Murphy, 2009: 153–156). Nay and Brunson’s (2013) survey demonstrates that MEDICINE metaphors may also effectively convince recipients to protect the forests (p. 165), as in the following: ‘An ecological system is healthy and free from distress syndrome if it is stable and sustainable’ (Ross et al, 1997: 119). MEDICINE metaphors can promote compassion among recipients who can interpret environmental disruption according to their own experience of sickness (Augé, 2021).…”
Section: Climate Change and Metaphorsmentioning
confidence: 99%